The p90 Ribosomal S6 Kinase (RSK) Is a Mediator of Smooth Muscle Contractility - Artamonov, Mykhaylo (Public Library of Science, 2013)
In the canonical model of smooth muscle (SM) contraction, the contractile force is generated by phosphorylation of the myosin regulatory light chain (RLC(20)) by the myosin light chain kinase (MLCK). Moreover, phosphorylation of the myosin targeting subunit (MYPT1) of the RLC(20) phosphatase (MLCP) by the RhoA-dependent ROCK kinase, inhibits the phosphatase activity and consequently inhibits dephosphorylation of RLC(20) with concomitant increase in contractile force, at constant intracellular [Ca(2+)]. This pathway is referred to as Ca(2+)-sensitization. There is, however, emerging evidence suggesting that additional Ser/Thr kinases may contribute to the regulatory pathways in SM. Here, we report data implicating the p90 ribosomal S6 kinase (RSK) in SM contractility. During both Ca(2+)- and agonist (U46619) induced SM contraction, RSK inhibition by the highly selective compound BI-D1870 (which has no effect on MLCK or ROCK) resulted in significant suppression of contractile force. Furthermore, phosphorylation levels of RLC(20) and MYPT1 were both significantly decreased. Experiments involving the irreversible MLCP inhibitor microcystin-LR, in the absence of Ca(2+), revealed that the decrease in phosphorylation levels of RLC(20) upon RSK inhibition are not due solely to the increase in the phosphatase activity, but reflect direct or indirect phosphorylation of RLC(20) by RSK. Finally, we show that agonist (U46619) stimulation of SM leads to activation of extracellular signal-regulated kinases ERK1/2 and PDK1, consistent with a canonical activation cascade for RSK. Thus, we demonstrate a novel and important physiological function of the p90 ribosomal S6 kinase, which to date has been typically associated with the regulation of gene expression.